Teachers’ perceptions about the difficulties in teaching grammar in an efl context, at the Technical University of Cotopaxi. - Musuña Masabanda, Maryuri Mariela (2024)
Teaching grammar has always been one of the most controversial and least understood topics in language teaching, since this can be taught explicitly or implicitly. In this sense, Grammar is a set of structural rules that are used to correctly form a sentence, allowing you to speak and write correctly to communicate with other people. Therefore, the objective of the project is to determine teachers' perceptions of the difficulties of teaching grammar in an English as a Foreign Language (EFL) context in the career Pedagogy of National and Foreign Languages-English major at Technical University of Cotopaxi. The study applied a qualitative approach and descriptive method. A semi-structured interview was employed for data collection, consisting of nine questions related to the difficulties presented by teachers when grammar teaching. 3 English teachers in career before mention participated in the study, who were interviewed and helped to obtain detailed information about their views and experiences in relation to the topic. In this study three categories were involved